Integrated 18F‐fluorodeoxyglucose positron emission tomography and computerized tomography in endodermal sinus tumor. Issue 4 (1st July 2006) - Klieger, C.; Dvir, R.; Even-Sapir, E.; Lessing, J. B.; Burstein, Y.; Grisaru, D.
Abstract : Application of an in-line positron emission tomography and computerized tomography (PET-CT) in endodermal sinus tumor (EST) is described in this study. Case 1: A young female with massive ascites postovarian mass resection had elevated alpha-fetoprotein (AFP) serum levels. Following a positive PET–CT study with increased 18 F-fluorodeoxyglucose (FDG) uptake, a CT-guided core biopsy of a peritoneal mass was performed. EST was diagnosed histologically. The patient was disease free after chemotherapy. Follow-up PET–CT was negative in keeping with no viable tumor tissue. Case 2: A large pelvic mass diagnosed histologically as primarily EST was removed in a teenage patient with elevated AFP levels. PET-CT showed diffuse abdominal spread of FDG uptake, suggesting extensive peritoneal seeding. The patient was disease free after chemotherapy. Follow-up PET-CT was negative. EST is an FDG-avid tumor. PET–CT delineated the prechemotherapy tumor extent adequately ruled out the presence of residual tumor after a successful treatment.